Is Artificial Intelligence Transforming Dentistry Today? - Saman Tauqir (Journal of Gandhara Medical and Dental Sciences, 2021)
Since the birth of science, the most fascinating structure of the human body is the human brain.  Over the past centuries’ researchers have been developing the latest technologies to imitate and explore how the human brain functions. However, to develop a machine that thinks like a human brain is still a dream for researchers. Aristotle’s early efforts to devise logical thinking via his syllogisms (a three-part deductive reasoning) were a source of inspiration for modern computers and technologies1. In the1950, Alan Turing designed a machine to decode encrypted messages, which was a breakthrough of super computers in the days of yore. He designed the “Turing Test” which was coined to assess whether a computer could exhibit intelligence better known as “artificial intelligence” (AI) today2. AI is “a field of science and engineering concerned with the computational understanding of what is commonly called intelligent behavior, and with the creation of artifacts that exhibit such behaviour”3.